Accounting for Inequality in India: Evidence from Household Expenditures - J. Salcedo Cain; Rhoda Magsombol; Ajay Tandon (Asian Development Bank (ADB), 2008)
J. Salcedo Cain, Rana Hasan, Rhoda Magsombol, and Ajay Tandon examine the evolution of inequality in India between 1983 and 2004. Inequality levels were relatively stable between 1983 and 1993, but increased between 1993 and 2004, a period of relatively fast economic growth. While the increases in inequality have not precluded reductions in poverty, decompositions of inequality and its change suggest that for the benefits of economic growth to be spread wider, greater dynamism in Indian agriculture and manufacturing will be essential.
hdl:11540/1774
Keywords: 330; Privater Konsum; Soziale Ungleichheit; Indien